PENERAPAN KONTEN PEMBELAJARAN EKONOMI BERBASIS CANVA PADA SISWA SMA - Veronica Sjeuriken Mamuaja; Edwin Wantah; Gilly M. Tiwow (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The use of digital learning media has become an important strategy for improving the quality of economics education in secondary schools. This study aimed to determine the effectiveness of Canva-based economics learning content in improving students’ learning outcomes at SMA Negeri 2 Tondano. A quantitative approach with a quasi-experimental design was employed in this study. The sample consisted of 26 eleventh-grade students selected through purposive sampling, including 11 students in the control class and 15 students in the experimental class. Data were analyzed using the independent sample t-test and N-Gain analysis to examine differences in learning outcomes and the level of improvement following the intervention. The results revealed a significant difference between the learning outcomes of students in the experimental and control groups, with a significance value (Sig. 2-tailed) of 0.040 (< 0.05). In addition, the N-Gain analysis yielded an average score of 78.82%, which falls into the high category. These findings indicate that Canva-based economics learning content is effective in enhancing students’ learning outcomes. Canva facilitates the presentation of learning materials in a more engaging and interactive manner, thereby promoting greater student participation during the learning process. Therefore, Canva-based economics learning content can serve as an effective alternative learning medium for improving the economics learning outcomes of eleventh-grade students at SMA Negeri 2 Tondano. ABSTRAK Pemanfaatan media pembelajaran digital menjadi salah satu strategi yang dapat mendukung peningkatan kualitas pembelajaran ekonomi di sekolah menengah. Penelitian ini bertujuan untuk mengetahui efektivitas penerapan konten pembelajaran ekonomi berbasis Canva terhadap hasil belajar siswa di SMA Negeri 2 Tondano. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi experiment. Sampel penelitian berjumlah 26 siswa yang dipilih menggunakan teknik purposive sampling, terdiri atas 11 siswa pada kelas kontrol dan 15 siswa pada kelas eksperimen. Data dianalisis menggunakan uji t dan N-Gain untuk mengetahui perbedaan hasil belajar serta tingkat peningkatan yang terjadi setelah perlakuan. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara hasil belajar siswa pada kelas eksperimen dan kelas kontrol dengan nilai signifikansi (Sig. 2-tailed) sebesar 0,040 (< 0,05). Selain itu, hasil analisis N-Gain memperoleh rata-rata skor sebesar 78,82% yang termasuk kategori tinggi. Temuan ini menunjukkan bahwa penggunaan konten pembelajaran ekonomi berbasis Canva efektif dalam meningkatkan hasil belajar siswa. Media Canva mampu mendukung penyajian materi yang lebih menarik dan interaktif sehingga mendorong keterlibatan siswa dalam proses pembelajaran. Dengan demikian, penerapan konten pembelajaran ekonomi berbasis Canva dapat dijadikan alternatif media pembelajaran yang efektif untuk meningkatkan hasil belajar ekonomi siswa kelas XI di SMA Negeri 2 Tondano.